Esophageal defect repair by artificial scaffolds: a systematic review of experimental studies and proportional meta-analysis. Issue 3 (3rd October 2020) - Schizas, Dimitrios; Frountzas, Maximos; Sgouromallis, Emmanouil; Spartalis, Eleftherios; Mylonas, Konstantinos S; Papaioannou, Theodore G; Dimitroulis, Dimitrios; Nikiteas, Nikolaos
Abstract: Background: The traditional technique of gastrointestinal reconstruction of the esophagus after esophagectomy presents plenty of complications. Hence, tissue engineering has been introduced as an effective artificial alternative with potentially fewer complications. Three types of esophageal scaffolds have been used in experimental studies so far. The aim of our meta-analysis is to present the postoperative outcomes after esophageal replacement with artificial scaffolds and the investigation of possible factors that affect these outcomes. Methods: The present proportional meta-analysis was designed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and A MeaSurement Tool to Assess systematic Reviews guidelines. We searched Medline, Scopus, Clinicaltrials.gov, EMBASE, Cochrane Central Register of Controlled Trials CENTRAL, and Google Scholar databases from inception until February 2020. Results: Overall, 32 studies were included that recruited 587 animals. The pooled morbidity after esophageal scaffold implantation was 53.4% (95% CI = 36.6–70.0%). The pooled survival interval was 111.1 days (95% CI = 65.5–156.8 days). Graft stenosis (46%), postoperative dysphagia (15%), and anastomotic leak (12%) were the most common complications after esophageal scaffold implantation. Animals that underwent an implantation of an artificial scaffold in the thoracic part of their esophagus presented higher survival rates than animals that underwent scaffold implantation in the cervical or abdominal part of their esophagus ( P < 0.001 and P = 0.011, respectively). Conclusion: Tissue engineering seems to offer an effective alternative for the repair of esophageal defects in animal models. Nevertheless, issues like graft stenosis and lack of motility of the esophageal scaffolds need to be addressed in future experimental studies before scaffolds can be tested in human trials.